The structure of information technology of models identification and optimization of electric vehicles in conditions of constraints on time and speed and electricity consumption - Mokin, O. B. (Visnyk of Vinnytsia Politechnical Institute, 2010)
There had been suggested the structure of information technology model identification and optimization of electric vehicles, moving along the surface with complex relief, which takes into account: the need for their movement from stop to stop on a deterministic time schedule; a complex relief surface on which the track is laid; the constraints on the speed motion (including while driving on the path curvature on the descent and ascent); the need to overcome the distance between stops with the minimum electricity consumption.